Upaya Meningkatkan Kinerja Karyawan Dengan Efikasi Diri, Tingkat Pendidikan Melalui Kepuasan Kerja - Huda, Khasbulloh (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Companies face many problems related to employee performance, so many researchers are interested in studying and conducting research. This research aims to determine the direct influence between self-efficacy and education level on job satisfaction. They also know the direct influence of self-efficacy, level of education, and job satisfaction on employee performance. It also shows the role of job satisfaction in mediating the relationship between self-efficacy and education level on employee performance. The method in this research is research with a quantitative approach; the population used is all employees of P.T. Gansar Jaya, with a sample of 63 employees; for data analysis, using Structural Equation Modeling (S.E.M.) and Smart P.L.S. version 3.0 software. The results of this research show that self-efficacy and education level directly influence job satisfaction. Self-efficacy, education level, and job satisfaction directly influence employee performance. Meanwhile, self-efficacy has an indirect influence on employee performance through job satisfaction. The indirect effect of education level is that it influences performance through job satisfaction. Keywords: Self-Efficacy; Educational Level;, Job Satisfaction; Employee performance